Meditation the Way toward Faith (Salam International Academic Journal, 2022)
Since thinking is very important, scholars considered it worship and they deemed it as an effective way of amending the perception, belief, worldview, and behavior of human beings, so it can be considered the path to faith.    This research titled “Thinking the Way to Faith", includes the following topics: First, the literal and idiomatic meanings of “tafakkur”, its importance and virtue, and then the essence of thinking are discussed. Next, the types of thinking and its classification into acceptable and unacceptable, and its aspects are discussed in detail. Moreover, the methods of the Holy Qur'an about calling to thinking, and its obstacles are explained.  Then, the benefits and effects of thinking, which are one of the important aspects of this subject, are studied in detail. Finally, the paper is concluded by mentioning the outcomes of the research.